1995
DOI: 10.1165/ajrcmb.13.4.7546768
|View full text |Cite
|
Sign up to set email alerts
|

Induction of heme oxygenase-1 gene expression by lipopolysaccharide is mediated by AP-1 activation.

Abstract: Gram-negative sepsis is the most common cause of the adult respiratory distress syndrome (ARDS). Lipopolysaccharide (LPS) when administered in vivo produces pathophysiologic changes similar to those seen in ARDS. The pathogenesis of these changes is mediated in part by oxidative stress. We demonstrate that LPS induces high mRNA levels of the stress-inducible gene heme oxygenase-1 (HO-1) in the rat lung. Increased HO-1 mRNA levels correlate with increased HO-1 protein and enzyme activity. Immunohistochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
157
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(169 citation statements)
references
References 33 publications
9
157
3
Order By: Relevance
“…HO-3 is the least understood and may be a pseudogene, and at least in the rat, it has been suggested that there is no functional HO-3 gene (12). HO-1 can be induced by a variety of agents causing oxidative stress including heavy metals, cytokines, hormones, endotoxin, and heat shock (1,3,6,17,25). Emerging body of evidence indicates that HO-1, besides its role in heme degradation, serves as a key biological molecule in the adaptation response and defense against oxidative stresses, and it provides cytoprotection in a variety of in vivo and in vitro models of cellular and tissue inflammation and injury (33).…”
Section: Discussionmentioning
confidence: 99%
“…HO-3 is the least understood and may be a pseudogene, and at least in the rat, it has been suggested that there is no functional HO-3 gene (12). HO-1 can be induced by a variety of agents causing oxidative stress including heavy metals, cytokines, hormones, endotoxin, and heat shock (1,3,6,17,25). Emerging body of evidence indicates that HO-1, besides its role in heme degradation, serves as a key biological molecule in the adaptation response and defense against oxidative stresses, and it provides cytoprotection in a variety of in vivo and in vitro models of cellular and tissue inflammation and injury (33).…”
Section: Discussionmentioning
confidence: 99%
“…Although heme is the major substrate of HO-1, a wide variety of agents, including heavy metals, cytokines, hormones, endotoxin, and heat shock, has been identified as strong inducers of HO-1 expression (1,5,24,33). HO-1 is highly induced by various inflammatory stimulants and agents that cause oxidative stress, such as hydrogen peroxide, glutathione depletors, UV radiation, hyperoxia, and ischemia-reperfusion injury (5,18,22).…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 expression responds to stimulation by a number of chemical and physical effectors, including its physiological substrate heme, as well as heavy metals, ultraviolet radiation, oxidants, nitric oxide, thiol-reactive substances, and hyperoxic or hypoxic states (1,4,24). Furthermore, HO-1 responds to a number of cytokines, hormones, and related sub-stances, including proinflammatory mediators such as tumor necrosis factor-␣ (TNF-␣), interleukin-1 (IL-1), and bacterial lipopolysaccharide, the thrombopoietic cytokine IL-11, and growth factors, such as plateletderived growth factor and TGF-␤ 1 (5,16,21,24).…”
mentioning
confidence: 99%
“…16,18,27,28 Therefore, the effect of HX106N on the activation of Nrf2 and AP-1 was examined by assessing the nuclear accumulation of Nrf2 and c-Jun, a major component of the AP-1 family. BV-2 cells were treated with 1 mg/mL HX106N, and the nuclear proteins were extracted at various time points, followed by Western blot analysis to determine the levels of these two transcription factors.…”
Section: Effects Of Hx106n On Nrf2 and Ap-1 Activationmentioning
confidence: 99%